2019
DOI: 10.1590/1414-431x20198318
|View full text |Cite
|
Sign up to set email alerts
|

Poly(trimethylene carbonate-co-L-lactide) electrospun scaffolds for use as vascular grafts

Abstract: Currently, there is great clinical need for suitable synthetic grafts that can be used in vascular diseases. Synthetic grafts have been successfully used in medium and large arteries, however, their use in small diameter vessels is limited and presents a high failure rate. In this context, the aim of this study was to develop tissue engineering scaffolds, using poly(trimethylene carbonate- co -L-lactide) (PTMCLLA), for application as small diameter vascular grafts. For this, copolymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This observation could have been due to ECM production (as discussed in future sections) in the PCL/PTMC cell-cultured constructs, slightly increasing the mechanical properties. ,, Also, SEM imaging of the fibers in the PCL and PCL/PTMC constructs showed mild fiber degradation in the C-PCL/PTMC-LA layer, while no fiber degradation was observed in the PCL construct or the R-PCL/PTMC-CL layer of the PCL/PTMC construct (Figure c–f). This observation could be due to the relatively fast degradation of LA compared to CL and could have resulted in a mild decline in tensile properties in the circumferential direction of the PCL/PTMC constructs . However, after removing the ECM material from the PCL and PCL/PTMC constructs and weighing the acellular substrates after 1, 10, 20, and 30 days of cell culture, there was no change in the mass of the substrates (Figure g).…”
Section: Resultsmentioning
confidence: 97%
“…This observation could have been due to ECM production (as discussed in future sections) in the PCL/PTMC cell-cultured constructs, slightly increasing the mechanical properties. ,, Also, SEM imaging of the fibers in the PCL and PCL/PTMC constructs showed mild fiber degradation in the C-PCL/PTMC-LA layer, while no fiber degradation was observed in the PCL construct or the R-PCL/PTMC-CL layer of the PCL/PTMC construct (Figure c–f). This observation could be due to the relatively fast degradation of LA compared to CL and could have resulted in a mild decline in tensile properties in the circumferential direction of the PCL/PTMC constructs . However, after removing the ECM material from the PCL and PCL/PTMC constructs and weighing the acellular substrates after 1, 10, 20, and 30 days of cell culture, there was no change in the mass of the substrates (Figure g).…”
Section: Resultsmentioning
confidence: 97%
“…Teeth that naturally fall off in children and wisdom teeth that need to be extracted in adults both contain abundant DPMSCs. Braghirolli et al found that copolymers with different trimethylene carbonate/lactide ratios ES SDVGs supported the adhesion and growth of DPMSCs, umbilical cord blood EPCs, and primary aortic SMCs, and promoted the differentiation of DPMSCs into vascular SMCs ( Braghirolli et al, 2019 ). The same group also evaluated the effect of DPMSCs on another kind of SDVGs composed of heparin/VEGF-modified PCL ES fibers.…”
Section: Multipotent Stem Cells In Es/sc Sdvgsmentioning
confidence: 99%